Antibacterial activity of essential oil of Minthostachys mollis Griseb “RUYAQ MUÑA” - Carhuapoma Y., Mario (2009)
The aim of this study was to determine the antibacterial activity of essential oil Minthostachys mollis “ruyaq muña”, against Helicobacter pylori, Shigella dysenteriae, Salmonella typhi and Pseudomonas aeruginosa. The leaves of M. mollis were collected in the district of Huamanguilla (3000-3200 m.s.n.m), Huanta province, Ayacucho region. The essential oil obtained by distillation with water vapor drag. The antibacterial activity was determined by plate cultive excavation method, resulting in order of sensitivity, for S. dysenteriae 21.41 mm; H. pylori 17,07 mm; S. typhi 14.25 mm and P. aeruginosa 11.45 mm. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for H. pylori were determined by the microplate dilution method, resulting in 2 μg/mL. For the other bacteria was determined by the dilution method, being for S. dysenteriae 4 μg/ml, S. typhi 4 μg/ mL, and P. aeruginosa 9 μg/mL and MIC 10 μg/ml of CMB. The percentages of inhibition compared with ciprofloxacin, were: H. pylori 177,2;, S. dysenteriae 126,11; S. typhi 63,44 and P. aeruginosa 42,29 and compared with chloramphenicol: P. aeruginosa of 225,56; S. dysenteriae 171,97; S. typhi 135,95 and H. pylori 92.86. The essential oil density is 0,9029 g/mL, refractive index 1,56689 and the percentage yield 2.4 v/p. Was showed presence of phenols, which validate the antimicrobial activity of essential oil of M. mollis.